Le RAle Instrumental Et Incitatif Du Reporting Socital Dans La Gestion Des Rsultats (Global Journal of Management and Business Research, 2014)
This article discusses the impact of the disclosure of social information on the accounting manipulations. We support the idea that earnings management damages the interests of stakeholders, therefore, officers who handle the results can not cope with the vigilance and activism of stakeholders as the use of social responsibility (CSR). In addition, CSR is a powerful tool that can be used to gain the support of stakeholders. Based on a sample of 682 U.S. companies listed , the Fortune 1000 for the period 1997-2008, we were interested to show that disclosure of social information justifying the strategic use of CSR by the officer who handles accounting figures. Our results show that the accounting practices of societal leaders strengthen the management of results and influence its direction and intensity.
Keywords: earnings management; social reporting; governance; stakeholder theory